Fumigation of maize for weevil control using Tanaecium nocturnum (Bignoniaceae) - Fazolin, Murilo; Costa, Charles Rodrigues da; Damaceno, Janaína Estevo de Oliveira; Albuquerque, Elizângela Sampaio de; Cavalcante, Ana Suzette da Silva; Estrela, Joelma Lima Vidal (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to assess the effect of fumigating corn grains with injured stem parts of Tanaecium nocturnum in the control of Sitophilus zeamais. The experimental design was completely randomized with seven replicates in split plots. The plots consisted of fumigation treatments and the subplots, of consecutive time intervals taken every 23 days for the evaluations. The treatments were: fumigation using 50 g of green stem parts of T. nocturnum per kilogram of corn grains; which contained between 800 and 900 mg kg-1 HCN fumigation using 60 mg of aluminum phosphide tablets per kilogram of corn grains with 57% of active ingredient; and control (no fumigation). S. zeamais infestation and weight loss of corn grains were evaluated nine times along 207 days. The use of 50 g kg-1 of stem parts of T. nocturnum for S. zeamais control produced reduction of the pest infestation and of the weight loss of grains comparable to that of aluminum phosphide. This alternative control can be adapted to maize storage conditions on small properties in Occidental Amazon.